The relationship between the level of knowledge about cross-infection control and its compliance among students at jenderal achmad yani university dental hospital: Cross sectional study - Kamila, Syadza Afifah; Mulyanti, Sri; Utami, Ulfah; Nurnaningsih, Hera (Padjadjaran Journal of Dental Researchers and Students, 2024)
ABSTRACTIntroduction: Due to their frequent contact with blood and saliva while providing dental care, dental healthcare personnel are particularly vulnerable to infection transmission. According to a preliminary study, a large number of students have not yet put cross-infection control procedures into place, even though doing so may raise their risk of coming into contact with pathogens. The purpose of this research is to ascertain how students at the RSGM UNJANI relate to their level of cross-infection control knowledge and their compliance with its implementation. Methods: This type of research is analytical research with a cross-sectional research design with a sample of 60 students at UNJANI RSGM. Data collection using questionnaires and observation. Results: The results of the survey indicate that the students' knowledge levels fall into three categories: "good" at 23.3%, "sufficient" at 66.7%, and "poor" at 10%. According to the level of compliance, 20% are not in conformity, while 80% are. Using the statistical test of Kendall's Tau, the p-value was 0.047 (p < 0.05). The two variables have a unidirectional association, which means that higher knowledge corresponds to higher compliance with cross-infection control methods. Conclusion: The results of the Kendall's Tau statistical test indicate that there is a unidirectional association between students' compliance with the implementation of cross-infection control and their understanding of it. This means that the better the students' knowledge of cross-infection control, the higher their compliance in applying the infection control measures.KEY WORDS: Knowledge, compliance, cross-infection controlHubungan tingkat pengetahuan tentang pengendalian infeksi silang terhadap kepatuhan pelaksanaan pada peserta didik di RSGM Universitas Jenderal Achmad Yani: studi cross sectionalABSTRAKPendahuluan: Tenaga kesehatan gigi memiliki risiko tinggi dalam penularan infeksi karena berkontak dengan saliva dan darah saat perawatan gigi. Survei awal menunjukkan masih banyak peserta didik belum menerapkan pengendalian infeksi silang padahal hal ini dapat meningkatkan risiko terpapar mikroorganisme penyebab infeksi. Tujuan penelitian ini untuk menganalisis hubungan tingkat pengetahuan tentang pengendalian infeksi silang terhadap kepatuhan pelaksanaannya pada peserta didik di RSGM UNJANI. Metode: Jenis penelitian ini yaitu penelitian survei analitik dengan rancangan penelitian cross-sectional dengan sampel 60 orang peserta didik di RSGM UNJANI. Pengumpulan data menggunakan kuesioner dan observasi. Hasil: Penelitian menunjukkan tingkat pengetahuan peserta didik dengan kategori baik 23,3%, kategori cukup 66,7%, dan kategori kurang 10%. Tingkat kepatuhan didapatkan hasil 80% kategori patuh dan 20% kategori tidak patuh. Uji statistik Kendall’s-Tau menunjukkan hasil nilai p = 0,047 (p < 0,05). Hubungan kedua variabel bersifat satu arah, artinya semakin baik pengetahuan maka semakin baik pula kepatuhan terhadap pengendalian infeksi silang. Simpulan: berdasarkan temuan uji statistik Kendall's Tau, terdapat hubungan satu arah antara tingkat pengetahuan mahasiswa RSGM UNJANI mengenai pengendalian infeksi silang dengan kepatuhan pelaksanaannya, artinya semakin baik tingkat pengetahuan peserta didik mengenai pengendalian infeksi silang, maka semakin tinggi pula tingkat kepatuhan mereka dalam menerapkan langkah-langkah pengendalian infeksi silang tersebut.KATA KUNCI: Pengetahuan, kepatuhan, pengendalian infeksi silang.